Progress in wall turbulence 2 : understanding and modeling : [proceedings of the 2nd WALLTURB International Workshop held in Lille, France, June 18-20, 2014] /: understanding and modeling : [proceedings of the 2nd WALLTURB International Workshop held in Lille, France, June 18-20, 2014]. ([2016]) - Unknown
No abstract available